Pheochromocytoma-Induced Takotsubo Syndrome Treated With Extracorporeal Membrane Oxygenation: Beware of the Apical Sparing Pattern - Kiamanesh, Omid (JACC Case Rep, 2019)
A 45-year-old female presents with suspected acute myocardial infarction with cardiogenic shock requiring mechanical circulatory support. Pheochromocytoma-induced atypical Takotsubo syndrome is diagnosed. Clinicians should suspect high catecholamine states as a cause of the basal subtype of atypical Takotsubo syndrome. (Level of Difficulty: Beginner.)